A tri-national study of accountancy students' ethical attitudes / Conor O'Leary and Shafi Mohamad - O'Leary, Conor; Mohamad, Shafi (Faculty of Accountancy & Accounting Research Institute (ARI), 2006)
Ethics is an integral part of the accountancy profession. As the profession becomes more internationalized, it is critical to accept that different nations may still advocate differing treatments for similar issues. This study evaluates whether the accountants of tomorrow already display differences in their attitudes, based upon nationality. The attitudes of final year accountancy students from three countries, Malaysia, Australia and Ire land we re compared across some ethical scenarios. Significant differences were found to exist based upon nationality. When confronted with bribery/corruption scenarios, Malaysian students were most likely to refuse participation but do nothing about them. Australian students were more likely to inform the relevant authorities. Irish students were more likely to participate than their Malaysian and Australian counterparts. Malaysian students were more likely to cheat in an exam than participate in corruption, whereas Irish and Australian students were more likely to do the opposite. Hence, ethical attitudes are affected by nationalistic traits. The ramifications for professional training should therefore be considered.